Compressive failure modes and energy absorption in additively manufactured double gyroid lattices - Maskery, Ian; Aboulkhair, Nesma T.; Aremu, A.O.; Tuck, Christopher; Ashcroft, Ian (Elsevier, 2018)
Lattice structures are excellent candidates for lightweight, energy absorbing applications such as personal protective equipment. In this paper we explore several important aspects of lattice design and production by metal additive manufacturing, including the choice of cell size and the application of a post-manufacture heat treatment. Key results include the characterisation of several failure modes in double gyroid lattices made of Al-Si10-Mg, the elimination of brittle fracture and low strain failure by the application of a heat treatment, and the calculation of specific energy absorption under compressive deformation (16x106 J m-3 up to 50% strain). These results demonstrate the suitability of double gyroid lattices for energy absorbing applications, and will enable the design and manufacture of more efficient lightweight parts in the future.